Determining substitutability of cloud services supported by semantically extended type theory - Xian-qing WANG; Chang-qin HUANG; UOXuan LUO; Rui-hua NIE; Yong TANG; Xiao-yong MEI (Tongxin xuebao, 2016)
In cloud environments, the high dynamics and more service failures were great obstacles to cloud applications, service substitution was a key research issue and also was a main solution to these challenges. A method of determining substitutability of cloud services was proposed using type theory, in which session types were semantically extended for modeling the behaviors of cloud service, QoS such as price, reliabil ty were introduced as QoS type, and a series of subtyping rules were constructed for SST and QoST. After that, determining consistency and context compatibility of services were put into practice. The method was proved feasibly by a case determining, and the experimental results show that it brings higher success rate of execution.